Acute rhabdomyolysis following viral infection with coxsackie A4 in a 50-day-old infant with Fukuyama congenital muscular dystrophy. Issue 5 (May 2020) - Yamaguchi, Hiroshi; Taniguchi-Ikeda, Mariko; Nagase, Hiroaki; Ito, Yusuke; Tokumoto, Shoichi; Toyoshima, Daisaku; Enkhjargal, Sarantuya; Nishiyama, Masahiro; Awano, Hiroyuki; Kurosawa, Hiroshi; Kasai, Masashi; Maruyama, Azusa; et al.
Abstract: Background: Fukuyama congenital muscular dystrophy (FCMD), which is characterized by generalized muscle weakness, hypotonia, and motor delay during early infancy, gradually progresses with advanced age. Although acute rhabdomyolysis following infection in patients with FCMD has occasionally been reported, no studies have investigated rhabdomyolysis following viral infection in FCMD patients during early infancy. Case report: We report the case of a 50-day-old girl with no apparent symptoms of muscular dystrophy who developed severe acute rhabdomyolysis caused by viral infection, resulting in quadriplegia and respiratory failure therefore requiring mechanical ventilation. Brain magnetic resonance imaging incidentally showed the typical characteristics of FCMD, and FCMD was confirmed by genetic analysis, which revealed a 3-kb retrotransposon insertion in one allele of the fukutin gene and a deep intronic splicing variant in intron 5 in another allele. The virus etiology was confirmed to be Coxsackie A4. Conclusion: We report a severe case of acute rhabdomyolysis with the earliest onset of symptoms due to the Coxsackie A4 virus in a patient with FCMD. The present findings indicate that physicians should consider FCMD with viral infection a differential diagnosis if the patient presents with acute rhabdomyolysis following a fever.